Pengaruh Pengetahuan Mahasiswa Tentang Karakteristik Bank Syariah, Produk Bank Syariah Dan Prinsip Bank Syariah Terhadap Persepsi Mahasiswa Tentang Perbankan Syariah - Naufal Afif Rayhan (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
This research was conducted to determine the influence of student knowledge about the characteristics of sharia banks, sharia bank products and sharia banking principles on students' perceptions of sharia banking. This research uses a quantitative method approach. Data collection was carried out by distributing questionnaires to students of the economics and business faculty at Dharma Andalas University. In this research, the sample used was 116 students. Testing the research instrument uses validity and reliability tests with SPSS 21. The analysis technique used in this research is multiple linear regression analysis. Based on the research results, it is known that: 1) the student knowledge variable about the characteristics of sharia banks has a positive effect on students' perceptions of sharia banking. 2) the student knowledge variable about sharia banking products has a positive effect on students' perceptions of sharia banking. 3) the student knowledge variable about sharia banking principles has no effect on students' perceptions of sharia banking.